Shewanella infection of snake bites: a twelve-year retrospective study - Po-Yu Liu; Zhi-Yuan Shi; Chin-Fu Lin; Jin-An Huang; Jai-Wen Liu; Kun-Wei Chan; Kwong-Chung Tung (Clinics, 2012)
OBJECTIVE: Infections of snake bite wounds by Shewanella are rarely discussed in the medical literature. This study aims to characterize the presentation and management of Shewanella infections in snake bite wounds. METHOD: We retrospectively investigated the microbiology, clinical features, and outcomes of patients with Shewanella infected snake bite wounds admitted to a tertiary medical center from January 1998 to December 2009. RESULTS: Ten patients with Shewanella-infected snake bite wounds were identified. All of the snake bites were caused by cobras. The majority of patients had moderate to severe local envenomation and polymicrobial infections. Shewanella isolates are susceptible to ampicillin-sulbactam, piperacillin-tazobactam, third-and fourthgeneration cephalosporins, carbapenems, aminoglycosides, and quinolones but are resistant to penicillin and cefazolin. All of the patients examined had favorable outcomes. CONCLUSION: It is recommended that Shewanella infection be considered in snake bite patients, especially when patients present with moderate to severe local envenomation.